Developing a portable, high-speed, low-cost desktop photoacoustic tomography imaging system - Kalva, Sandeep Kumar (2019)
Photoacoustic tomography (PAT) is a non-invasive, hybrid biomedical imaging modal- ity. Conventional PAT system uses Nd:YAG-OPO laser as excitation source and a single-element ultrasound transducer (SUT) for detecting the generated photoacoustic (PA) waves from the imaging object. Usually Nd:YAG-OPO laser is bulky, heavy and needs an optical table to deliver non-fluctuating laser beam and it needs external op- tics (reflectors/prisms) to direct the laser beam onto the sample (there are portable OPO lasers from OpoTek, EKSPLA, and various other companies that do not require optical table but they are more expensive than conventional Nd:YAG-OPO lasers). Also, the detecting element of the SUT is placed at orthogonal direction to the laser illumination for deep tissue imaging. Due to this configuration, the length of the transducer body and the connecting cable requires a lot of space inside the water (coupling medium) tank, thereby, increasing the size of the PAT scanner area. All these (laser, additional optics, SUT alignment) make the whole PAT imaging system very large in size and non- portable. Therefore, it is limited to bench-side laboratory imaging purposes. Moreover, this Nd:YAG laser is very expensive and has low pulse repetition rate of (10-100) Hz. So, one SUT takes several minutes to acquire a single cross-sectional PA data. This in turn, inhibits real-time imaging. The acquired PA data using this SUT is reconstructed conventionally using a simple delay-and-sum algorithm to obtain cross-sectional PA images. When this technique is employed for reconstruction, there will be blurring in tangential direction due to the effect of SUT aperture size, thereby, resulting in the degradation in quality (poor tangential resolution) of the PA images, especially when the target is far from the scanning center.